Experimental investigation of pistacia lentiscus biodiesel as a fuel for direct injection diesel engine. (15th January 2016) - Khiari, K.; Awad, S.; Loubar, K.; Tarabet, L.; Mahmoud, R.; Tazerout, M.
Highlights: Biodiesel is prepared from Pistacia Lentiscus oil. Biodiesel yield is 94% when using 6:1 methanol/oil and 1% KOH catalyst at 50 °C. BSFC and NOx emissions have increased with the use of biodiesel and its blends. Biodiesel reduces significantly HC, CO and particulate emissions at high engine load. Abstract: Biodiesel is currently seen as an interesting substitute for diesel fuel due to the continuing depletion of petroleum reserves and the environment pollution emerging from exhaust emissions. The present work is an experimental study conducted on a DI diesel engine running with either pistacia lentiscus (PL) biodiesel or its blends with conventional diesel fuel. PL biodiesel is obtained by converting PL seed oil via a single-step homogenous alkali catalyzed transesterification process. The PL biodiesel physicochemical properties, which are measured via standard methods, are similar to those of diesel fuel. A single cylinder, naturally aspirated DI diesel engine is operated at 1500 rpm with either PL biodiesel or its blends with diesel fuel for several ratios (50, 30 and 5 by v%) and engine load conditions. The combustion parameters, performance and pollutant emissions of PL biodiesel and its blends are compared with those of diesel fuel. The results show that the thermal efficiency is 3% higher for PL biodiesel than for diesel fuel. The emission levels of carbon monoxide (CO), unburned hydrocarbon (HC) and particulate matter are considerably reduced at full engine load (around 25%, 45% and 17% respectively). On the other hand, the brake specific fuel consumption (BSFC) and the nitrogen oxide (NOx) emissions increase (around 10% and 4% respectively).